Fortification of modified Cassava Starch with Bacterial Polyglutamic Acid derived from Bacillus natto - Heroney, Hevenney Vianie; Swee Ling, Joanna Ho; Sulistyo, Joko (Bahasa Indonesia, 2025)
Fortification of cassava starch with bacterial polyglutamic acid (PGA) offers the potential to enhance its nutritional value. The fortified starch was determined for its physicochemical and functional properties after addition of varying levels PGA. The findings showed that with increasing PGA levels, there was a significant (p < 0.05) decrease in bulk density, swelling power, and viscosity (peak, trough, breakdown, setback, and final), while water and oil absorption capacities and solubility index increased. In addition, increasing PGA content significantly (p < 0.05) increased protein content approximately 48.71% and fat content 72.5%, while moisture and ash content decreased 13.10% and 8.1%, respectively. Scanning electron microscopy (SEM) showed obvious cracks in starch granules and increased binding of PGA protein molecules to the surface of starch granules, resulting in the formation of larger agglomerates. This study focused on the assessment of the effects of fortification of cassava starch with PGA bacteria on its functional and sensory properties.